Customer value as a tool for increasing company competitiveness - Kožená, Marcela; Jelínková, Lucie (STEF92 Technology Ltd., 2016)
In today's dynamic business environment companies trying to transform, to be competitive in the future. They realize that the trend towards high performance, oriented on competition, technology and human resources, cannot be achieved only by monitoring and managing financial measures based on past performance. Increasingly, therefore, begin to use for measuring company performance methods such as Balanced Scorecard, which comprise outside the traditional financial measures of past performance, also measure as a drivers of future performance. Given the current development in the area of performance measurement and management, when there is a transition from a simple performance measurement on complex performance management, it is necessary to look at a comprehensive performance management system as a tool for connecting, learning and improvement. Performance management system should be basically a "living organism", he should be able to respond to changes in the dynamic and rapidly changing business environment. In this context, it is necessary to constantly improving the performance management system. In actual literature you can find countless different instruments contributing to more effective performance management system, identified and verified in the corporate practice of large foreign companies. Which specific tools and in what areas can then be used within a performance management system to make it more efficient? The aim of this paper is to identify and analyse possible tools or group of tools that can be used to streamline performance management system as a whole. Through a survey carried out on a sample of large manufacturing and non-manufacturing businesses operating in the Czech Republic, it is determined whether the management of the surveyed companies is able to identify tools affecting the implementation and continuous improvement of the performance management system.
Hodnota zákazníka jako nástroj pro zvyšování konkurenceschopnosti podniku
Keywords: customer value; company; competitiveness; customer relationship management; hodnota zákazníka; společnost; konkurenceschopnost; řízení hodnoty zákazníka